The Family of Francis Marion Shaw Newsletter Volume 1 Number 1 - Shaw, Bryan Lee (My University, 1993)
The issue honors the life of Francis Marion Shaw, a Confederate soldier who lost his right arm in the Civil War, and his wife Rachel Moore Allen Shaw, highlighting their resilience, compassion, and legacy. The newsletter includes family group sheets, biographical sketches of descendants, and appeals for historical contributions and unidentified family photographs.
This item contains 1 PDF with 4 pages and a title page in addition to 4 JP2 files.
Keywords: Berrien County Historical Foundation (Nashville; Ga.); Nashville (Ga.); Berrien County (Ga.); Newsletters; Periodicals; Berrien County (Ga.)--History--Sources; Electronic records; Grady County (Ga.)--History; Historic preservation--Georgia--Berrien County; Georgia--Genealogy